2023
DOI: 10.3390/genes14050969
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Characterization and Gene Changes Induced by Fusarium solani in Sweetpotato Roots

Abstract: Sweetpotato (Ipomoea batatas) is an important root crop that is infected by Fusarium solani in both seedling and root stages, causing irregular black or brown disease spots and root rot and canker. This study aims to use RNA sequencing technology to investigate the dynamic changes in root transcriptome profiles between control check and roots at 6 h, 24 h, 3 days, and 5 days post-inoculation (hpi/dpi) with F. solani. The results showed that the defense reaction of sweetpotato could be divided into an early ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Different studies were conducted to identify the key genes involved in disease resistance as well as genes induced by other pathogens in sweet potatoes. The RNA sequencing technology was used to investigate the dynamic changes in root transcriptome profiles at different root development stages after infection with Fusarium solani and identified several candidate genes related to plant-pathogen interaction and TFs that could be used to increase the biotic resistance in sweet potato [ 118 ]. De novo transcriptome assembly and digital gene expression profile of sweet potato identified various differentially expressed genes during defense, such as chitin elicitor receptor kinase-1, MAPK, NAC, WRKY, MYB, ERF TFs, as well as resistance, pathogenesis, SA and JA signaling pathways related genes against Fusarium wilt [ 119 ].…”
Section: Role Of Sweet Potato Transcriptomics For Incorporating Stres...mentioning
confidence: 99%
“…Different studies were conducted to identify the key genes involved in disease resistance as well as genes induced by other pathogens in sweet potatoes. The RNA sequencing technology was used to investigate the dynamic changes in root transcriptome profiles at different root development stages after infection with Fusarium solani and identified several candidate genes related to plant-pathogen interaction and TFs that could be used to increase the biotic resistance in sweet potato [ 118 ]. De novo transcriptome assembly and digital gene expression profile of sweet potato identified various differentially expressed genes during defense, such as chitin elicitor receptor kinase-1, MAPK, NAC, WRKY, MYB, ERF TFs, as well as resistance, pathogenesis, SA and JA signaling pathways related genes against Fusarium wilt [ 119 ].…”
Section: Role Of Sweet Potato Transcriptomics For Incorporating Stres...mentioning
confidence: 99%
“…Although only one QTL mapping study was conducted to identify the QTL for Fusarium root rot resistance with simple sequence repeat (SSR) markers for F 1 populations, a few QTL were identified but remained unverified because of the lack of related data and the small number of markers (n = 300) ( Ma et al., 2020 ). Recently, transcriptome analysis for sweet potato roots infected by F. solani showed that the number of upregulated genes was lower than that of downregulated genes such as calcium-binding protein, and many homologous genes, including 43 WRKY genes and 57 genes from the MYB family of proteins, were differently or inconsistently expressed, suggesting that genetic studies in sweet potatoes are challenging ( Zhang et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%